Nephrocolic Fistula in a Compromised Urinary Tract : A Case Identified via Radioisotope Mercaotiacetyltriglycine (MAG3) Diuretic Renography - Hsin Yen Tan; Kavesha Karunakaran; Nadiah Abd Razak; Ahmad Zaid Zanial; Charng Chee Toh (Department of Urology, Faculty of Medicine, Universitas Brawijaya, 2026)
Introduction. Nephrocolic fistula is an abnormal communication between the kidney and colon. It is rare and the presentation may be atypical. Diagnosis is usually made using retrograde pyelograde, CT scan or barium enema. Case. We present the case of a nephrocolic fistula detected on a radioisotope renography (MAG3) scan in a 74-year-old woman, who has a poorly controlled diabetes mellitus with a dysfunctional urinary tract due to recurrent emphysematous pyelonephritis (EPN) of the left kidney, complicated by a left ureteric stricture, pyonephrosis and neurogenic bladder secondary to diabetic cystopathy. She underwent multiple ureteric stentings, drainage procedures, and prolonged antimicrobial treatments for multidrug-resistant and fungal urosepsis. A renal MAG3 scan later revealed abnormal tracer accumulation in the descending colon, suggestive of a nephrocolic fistula. This case underscores the diagnostic challenges of nephrocolic fistula in individuals with a compromised urinary tract. Conclusion. Urologists should maintain a high index of suspicion for nephrocolic fistula particularly in individuals with a compromised urinary tract. Alternative diagnostic imaging may be utilized to establish the diagnosis.